2021
DOI: 10.3390/jcm10132846
|View full text |Cite
|
Sign up to set email alerts
|

Conduction Disorders during Sinus Rhythm in Relation to Atrial Fibrillation Persistence

Abstract: Classification of atrial fibrillation (AF) is currently based on clinical characteristics. However, classifying AF using an objective electrophysiological parameter would be more desirable. The aim of this study was to quantify parameters of atrial conduction during sinus rhythm (SR) using an intra-operative high-resolution epicardial mapping approach and to relate these parameters to clinical classifications of AF. Patients were divided according to the standard clinical classification and spontaneous termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In contrast, no differences in the conduction velocity between the SR and AF groups in the pulmonary vein area (PVA) were encountered [33]. Moreover, persistent AF is related to a higher number of conduction disorders at BB, prolonged P wave duration, and lack of spontaneous termination [34].…”
Section: The Role Of Interatrial Conductionmentioning
confidence: 99%
“…In contrast, no differences in the conduction velocity between the SR and AF groups in the pulmonary vein area (PVA) were encountered [33]. Moreover, persistent AF is related to a higher number of conduction disorders at BB, prolonged P wave duration, and lack of spontaneous termination [34].…”
Section: The Role Of Interatrial Conductionmentioning
confidence: 99%
“…Interatrial block (IAB) often occurs when a conduction delay occurs over Bachmann’s bundle or between the activation of the atrium. IAB was initially classified by Bayes de Luna and has recently often been defined according to IAB severity ( Bayés de Luna et al, 2018 ; van der Does et al, 2021 ). Partial IAB is defined as a P-wave duration over 120 ms, and advanced IAB is defined as a P-wave morphology (positive/negative) in II, III, and aVF with a duration ≥120 ms. Advanced IAB has been reported as being associated with both new-onset and recurrent atrial fibrillation, left atrial electromechanical dysfunction, ischemic stroke, and cardiovascular mortality in some clinical scenarios ( O'Neal et al, 2016a ; Fujimoto et al, 2018 ; Rubio Campal et al, 2018 ; Lacalzada-Almeida et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, classification based on intra-operative epicardial measurements is done using features like conduction block (CB) and continues conduction delay and block (cCDCB). However, these parameters do not clearly differentiate PAF and PsAF in sinus rhythm (SR) [5,6]. Van der Does et al showed that among all locations, only at Bachmann's bundle (BB) there is a higher number of cCDCB line (p-value=0.040), though [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these parameters do not clearly differentiate PAF and PsAF in sinus rhythm (SR) [5,6]. Van der Does et al showed that among all locations, only at Bachmann's bundle (BB) there is a higher number of cCDCB line (p-value=0.040), though [5]. However, the CB and cCDCB rely on an estimate of the local activation time (LAT).…”
Section: Introductionmentioning
confidence: 99%